Peran Corporate Governance Memoderasi Hubungan Audit Internal dengan Pendeteksian Kecurangan Laporan Keuangan - Shally Khomilah; Dwi Fitrianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of internal audit on the detection of fraudulent financial statements and examine the role of corporate governance in moderating the relationship in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2023–2024 period. Fraudulent financial reporting remains a serious issue in SOEs, indicating weaknesses in internal supervision and corporate governance implementation. Therefore, internal audit and corporate governance are expected to play an important role in improving fraud detection effectiveness. This research uses a quantitative method with an associative approach. The data used are secondary data obtained from annual reports and financial statements of SOEs listed on the Indonesia Stock Exchange. The sampling technique applied was purposive sampling, resulting in 14 companies with 28 observation data during the research period. Data analysis was conducted using panel data regression with the assistance of EViews 12 software. The results indicate that internal audit has an effect on the detection of fraudulent financial statements. In addition, corporate governance is able to moderate the relationship between internal audit and fraudulent financial statement detection. Strong corporate governance implementation strengthens the effectiveness of internal audit in detecting indications of fraud in financial reporting. These findings imply that companies need to improve the quality of internal audit functions and strengthen corporate governance practices to minimize the risk of financial statement fraud. This study contributes to the literature on internal audit, corporate governance, and fraud detection, particularly in the context of Indonesian SOEs.